UPAYA PENERAPAN DISIPLIN KERJA TERHADAP KEBERLANGSUNGAN KINERJA KARYAWAN PADA UPTD. KPH BALI SELATAN - Leni Setia Ningsih; Putu Purnama Dewi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2022)
Enforcing work discipline is an important thing for an institution or organization, because with the existence of work discipline, it is expected that most of the regulations made will be obeyed by employees. Reminding each other is important in working, if by reminding each other that there are still mistakes repeatedly, then the superior has the right to take strict action against employees who like to violate the rules. Employee work discipline can be carried out properly on the awareness from within the employee of the importance of the meaning of work discipline and with the existence of clear and firm regulations in its implementation. Therefore, human resources in every company must have quality values in carrying out work discipline. The purpose of devotion to UPTD. KPH South Bali is to provide an understanding to employees about the importance of obeying the regulations contained in the agency. The method used in this devotion is through a qualitative method by collecting data through observational observations at the place of devotion. The results of the service show that there is still a lack of awareness of UPTD employees. KPH South Bali in enforcing work discipline. So it is expected that UPTD employees. KPH South Bali can increase its awareness of the importance of work discipline in work.